NATIONAL IDEA AS THE BASIS OF THE POLITICAL MYTHOLOGY OF UKRAINE - Kovalevska, Tetiana (Public Management and Policy, 2025)
The article presents a systematic analysis of the Ukrainian national idea as a fundamental factor in the political mythology of Ukraine. The conceptual approaches to defining the national idea, its structural characteristics, and its functional significance in socio-political processes are explored. The role of the national idea in shaping collective identity, mobilizing society, and ensuring its consolidation in the context of internal transformations and external challenges is identified. Special attention is paid to the mechanisms of mythologization of the national idea, its reflection in political communication, ideological constructs, information campaigns, and the digital space. The influence of political myth-making on the narrative structure of the national idea, its adaptation to historical and socio-cultural contexts, is also examined. A critical analysis of the classical concepts of the Ukrainian national idea, as presented in the works of M. Drahomanov, D. Dontsov, V. Lypynsky, M. Hrushevsky, M. Mikhnovsky, and contemporary studies on the topic, is provided. The main approaches to defining the Ukrainian national idea are distinguished, including the state-building, axiological, consolidating, and Eurocentric approaches. It is concluded that these approaches are not mutually exclusive but, on the contrary, complement each other, which determines the multi-vector nature of the Ukrainian national idea. A special emphasis is placed on transforming the Ukrainian national idea in the context of the war with Russia. The process of its mythologization as a mobilizing factor is examined, as it forms heroic narratives, strengthens national identity, and promotes societal cohesion in the face of external aggression threats. It is concluded that the Ukrainian national idea is a dynamic concept that adapts to changing historical circumstances, performs integration and mobilization functions, and remains a key element of Ukraine’s political mythology. A promising direction for future research is the development of theoretical foundations for a universal model of the Ukrainian national idea, capable of ensuring the integrity of the political nation and effectively responding to the challenges of the globalized world.